Sustainability, Retail and Supply Chains: Twenty Years of Research - Graciola, Ana Paula; Rizzon, Fernanda; Milan, Gabriel Sperandio; De Toni, Deonir; da Rocha, Jefferson Marçal; Olea, Pelayo Munhoz (Revista de Negócios, 2018)
Retailers play the role of intermediaries between suppliers and customers. As key players in the market, retail managers, pressured to change their business based on sustainable development principles, they need to adjust their daily practices and disseminate information about their impacts and contributions to the sustainable development of their companies. Therefore, the main aim of this study was to understand the relations between the terms: sustainability, retail and supply chains by reviewing the literature in two databases: Scopus and Science Direct. As results, there has been an increase in studies related to the themes in the last 20 years. The areas with the highest concentration of studies are: Operations, Marketing, Consumer Behavior, Government Policies and Certifications. As contributions of the study, the following topics were highlighted for future research: Collaboration, Waste, Consumer Behavior, Value Creation, Communication, On-line Commerce, Retail Planning, Logistics, Product Lifecycle, Remanufacturing, Gas Emission, Certifications, Technology and Information Systems, and Environmental Policies.